The HCCH Judgments Convention in Australian Law. (September 2019) - Douglas, Michael; Keyes, Mary; McKibbin, Sarah; Mortensen, Reid
In May 2018, the Hague Conference on Private International Law ('HCCH') produced a draft convention for the recognition and enforcement of foreign judgments. A Diplomatic Session of the HCCH is expected to take place in 2019 at which this draft 'Judgments Convention' will be presented. If a multilateral convention emerges from the Diplomatic Session, Australia is likely to be an early adopter: the Commonwealth Attorney-General's Department conducted a public consultation on the draft Judgments Convention in 2018. Against that background, this article considers the impact of implementation of the Judgments Convention in Australia. It is argued that domestic legislation that emerges from the Judgments Convention will deliver an overdue refurbishment of the Australian law relating to the recognition and enforcement of foreign judgments. Australia's adoption of the Judgments Convention ought to be welcomed.